OLIGARCHIC CAPTURE OF CONSTITUTIONAL DEMOCRACY: A SOCIO-LEGAL LITERATURE REVIEW - Iskandar Syukur (Journal of Social and Economics Research, 2025)
The practice of constitutional democracy demonstrates a tendency toward an increasingly strong concentration of power in the political and legislative processes. The influence of powerful economic actors and interconnected interests within state institutions contributes to shaping policy directions that do not fully reflect the broader public interest. This situation is reinforced by the formation of public narratives that influence public perceptions and support the legitimacy of existing power. This study aims to examine how these practices reflect an imbalance of influence in the implementation of constitutional democracy. This research uses a qualitative approach based on a socio-legal literature review, utilizing various relevant sources. The results show that the concentration of power, interference with the independence of state institutions, and policy distortions form interrelated and recurring patterns. The direction of public policy tends to reinforce certain interests, while accountability and participation mechanisms are not functioning optimally. The formation of public narratives plays a role in maintaining the legitimacy of power, thereby narrowing the scope for correction of practices that align with the broader public interest.